Case Report: Acute pyelonephritis and hearing loss in scrub typhus - Venketesan, Sivaranjini (F1000Res, 2019)
Acute pyelonephritis is a common renal manifestation in patients with diabetes. A 52-year-old diabetic lady presented with loin pain, dysuria, and fever and urinary incontinence that had begun seven and three days prior to presentation respectively. She was treated with escalating spectra of intravenous antibiotics without improvement. Urine and blood cultures were sterile, while radiological investigations were suggestive of pyelonephritis. Mild hepatic dysfunction prompted consideration of scrub typhus and she improved with empirical doxycycline. Scrub IgM was later confirmed to be positive. In conclusion, local prevalence of systemic infections such as rickettsioses should always be considered in diabetics with fever, even if symptoms and signs otherwise suggest typical diabetes-related infections. We, therefore report a case of acute pyelonephritis caused by scrub typhus which has not been previously described in English medical literature.